2023
DOI: 10.1111/pace.14659
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and safety of high‐power ablation guided by Lesion size index: An ex vivo porcine heart study

Abstract: Background Although Lesion size index (LSI) has been reported to highly predict radiofrequency lesion size in vitro, its accuracy in lesion size and steam pop estimation has not been well investigated for every possible scenario. Methods Initially, radiofrequency ablations were performed on porcine myocardial slabs at various power, CF, and time settings with blinded LSI. Subsequently, radiofrequency power at 20, 30, 40, 50, and 60 W was applied at CF values of 5, 10, 20, and 30 g to reach target LSIs of 4, 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Recently, researchers have noticed the role of SLC31A1 in cardiomyopathy. One study reported that SLC31A1-related signaling pathways may be involved in the pathogenesis of diabetic cardiomyopathy [39]. MAP2K1 is a member of the dual specificity protein kinase family and is an important part of the intracellular and extracellular MAP kinase signaling pathway, which is involved in many biological processes such as cell proliferation and differentiation [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have noticed the role of SLC31A1 in cardiomyopathy. One study reported that SLC31A1-related signaling pathways may be involved in the pathogenesis of diabetic cardiomyopathy [39]. MAP2K1 is a member of the dual specificity protein kinase family and is an important part of the intracellular and extracellular MAP kinase signaling pathway, which is involved in many biological processes such as cell proliferation and differentiation [40].…”
Section: Discussionmentioning
confidence: 99%